NONLINEAR AGROMETEOROLOGICAL MODELS FOR ESTIMATING LYCHEE FRUIT GROWTH - LUCAS EDUARDO DE OLIVEIRA APARECIDO; RAFAEL BIBIANO FERREIRA; GLAUCO DE SOUZA ROLIM; BIANCA SARZI DE SOUZA; PAULO SERGIO DE SOUZA (Revista Brasileira de Fruticultura)
ABSTRACT The influence of climate on the development of lychee fruit is complex, but few studies have discussed the problem. We developed agrometeorological models for simulating the development of fruit fresh matter (FM), fruit dry matter (DM), fruit length (LE), fruit diameter (DI), fruit volume (VO), and fruit number per cluster (FN) of the “Bengal” lychee cultivar as functions of climatic conditions. We conducted three analyses: (a) the influence of mean meteorological elements on the rates of fruit growth, (b) estimation of fruit development by the agrometeorological models using sigmoidal adjustments, and (c) simulation of fruit development using multiple nonlinear regression of two meteorological elements to improve the accuracy. A rate of water deficit (WD) near 5 mm d-1 maximised FM, DM, LE, DI, and VO. Increases in potential evapotranspiration (PET), degree days (DD), and actual evapotranspiration (AET) were correlated with increases in VO and decreases in LE and NF. Models estimating fruit development indicated that the accumulation of WD, PET, AET, and DD had sigmoidal relationships with all variables of fruit growth except FN. FN decreased as WD, PET, AET, and DD increased. The adjusted multivariate models were accurate, with the largest error of 6.45 cm3 (VO). The best models were: FM = f(SWD, DD), LE = f(SAET, DD), DI = f(SWD, DD), VO = f(SWD, DD), and FN = f(SAET, WD).